Peningkatan Nilai Tambah Produk Olahan Gula Aren Melalui Inovasi Kemasan dan Pemanfaatan Media Sosial Sebagai Strategi Pemasaran di Desa Aik Bual Kecamatan Kopang - Novia Rizki Warismayati; Halimatul Ulfa Ru’ya; Windi Irawati; Baiq Novianti Dili Hairunnisa; Bambang Budi Santoso Santoso (Fakultas Pertanian Universitas Mataram, 2020)
Aik Bual village is located in Kopang sub-district, Central Lombok district. In this village, there are many palm trees that grow in gardens and forests. Most of the people use palm sugar to be processed into palm sugar. Palm sugar production by the Aik Bual community is carried out individually in their homes and there is also a joint business group (KUBE) that has been formed and already has a certificate from the village namely KUBE Salanumpang Aren. The aim of this program is to increase the added value of processed palm sugar products through packaging innovation and the use of social media as a marketing strategy. The method used is socialization, counseling, as well as training and assisting producers of palm sugar business groups. Furthermore, the socialization event took place at the Aik Bual Village Office, which was attended by a joint business group of Salanumpang Aren who are Aik Bual people as active actors in making palm sugar, while the activity was attended by parties from the village such as Village Owned Enterprises (BUMDes) and village officials. Through this program it is hoped that the community, especially KUBE Salanumpang Aren in Aik Bual Village, will be able to increase the added value of processed palm sugar products through packaging innovation and the use of social media as a marketing strategy in Aik Bual Village, Kopang sub-district